INFLUENCE OF ORGANIZATIONAL COMMITMENT AND PSYCHOLOGICAL CONTRACT ON EMPLOYEE PERFORMANCE RSUD A. YANI METRO CITY, LAMPUNG - Anjali Nonce Dimara; Habibullah Jimad (Sekolah Tinggi Ilmu Syrari’ah Daru ‘Ulum (STSDU) Lampung Timur., 2022)
The health agency is a service that requires experts in providing services. Therefore, health agencies are competing to meet the main requirements, namely qualified medical personnel with the right standards. This research aims to determine the effect of organizational commitment and psychological contract on employee performance partially and simultaneously, with 202 civil servant employees at A. Yani Metro Lampung Hospital as subjects. The method used in this research is a questionnaire/questionnaire and literature study, with data testing techniques in the form of validation tests, reliability tests, multiple linear regression (t test and F test). The results of the research show that partially and simultaneously there is a positive influence between organizational commitment and psychological contract on employee performance. So it can be interpreted that when the organizational commitment and psychological contract of an employee are high it will affect the higher the employee's performance results, conversely when the organizational commitment and psychological contract of an employee are low it will influence and have an impact on the low performance results of the employee.